An Autopsy Case Report of an Infant Born to a Diabetic Mother, With Review of Literature—A Pandora’s Box of Pathologies - Gurpreet Kaur; Raghav Sharma; Vikram Singh; Ankur Ahuja; Somasundaram Venkatesan (Case Reports in Pathology, 2025)
Gestational diabetes mellitus (GDM) affects approximately 2%–17.8% of pregnancies, with preexisting diabetes also contributing to significant fetal risks. Despite advancements in obstetric and medical care, pregnancies complicated by maternal diabetes continue to carry a higher likelihood of fetal loss compared to nondiabetic pregnancies. Infants born to diabetic mothers (IDMs) are predisposed to complications such as birth trauma, respiratory difficulties, metabolic derangements including hypoglycemia and hypocalcemia, jaundice, increased blood viscosity, and various congenital anomalies—all potentially contributing to fetal mortality. We report the autopsy findings of a male IDM, born to a 25-year-old primigravida conceived via intrauterine insemination (IUI) with GDM, delivered at 38 weeks and 3 days of gestation, weighing 3.1 kg with reassuring Apgar scores at birth. Despite an apparently uncomplicated delivery and no immediate congenital anomalies detected, the infant developed sudden respiratory distress and unresponsiveness at 90 min of life, leading to unsuccessful resuscitation efforts. The autopsy revealed hallmark features of maternal–fetal glucose imbalance, including cardiopulmonary hypertrophy, hepatomegaly, immature lungs, pulmonary hypertension, and marked pancreatic islet cell hyperplasia. Inflammatory changes in the meninges and hypoxic neuronal injury were also observed. No structural malformations were identified. Although neonatal autopsies are inherently challenging, they provide critical insights that may influence neonatal care practices and guide future genetic counseling for affected families.